SOLUSI EKONOMI ISLAM TERHADAP DISTRIBUSI HARTA - Hamda Sulfinadia (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2015)
Abstract Meaning of distribution in the wider Islamic economics, which includes ownership arrangements elements of production and sources of wealth. Islam allow common ownership and specific ownership and put to each of the two kaedah-kaedah to inheritance, grants and testament. Islamic Economics comes with a distribution system that realizes a variety of purposes that include various areas of life and has contributed along sysri'ah political system and others in realizing the common objectives of Shariah. The purpose of distribution in Islamic economics can be grouped for purposes of propaganda, education, social and economic. Distribution of justice in Islam is necessary, in order to prevent the accumulation of wealth. There are three ways you can do to penyesuaikan melestrikan differences and economic balance between the individuals in the community or state. First, do not allow accumulation or hoarding of wealth and ensure the availability of community needs any nationality or religion, and do not spend money or property to luxury. Second, do not let the circulation of wealth only in a minority. Third, Islam does not allow the imbalance in the distribution of wealth and income, which would upset the balance of the economy. However, the discrepancy can provide motivation for creativity and initiative to achieve integration and cooperation not bring up the differences and conflicts. Kata Kunci: Distribusi, Ekonomi Islam, Harta